Teen Pregnancy, Depression, and Substance Abuse: The Conditioning Effect of Deviant Peers. Issue 3 (4th March 2021) - Walker, D'Andre; Holtfreter, Kristy
ABSTRACT: General Strain Theory (GST) suggests that individuals who experience strain are pressured into criminal and deviant behavior. Consistent with GST, the current study assesses the relationship between strain in the form of teenage pregnancy and substance use behavior, specifically alcohol problems and marijuana use. In addition, deviant peer association is a robust predictor of criminal behavior, therefore, we also investigate the role of deviant peers in the coping process among females who experience teenage pregnancy. Data for the analysis were obtained from Waves I and II of the National Longitudinal Study of Adolescents to Adult Health (Add Health). In a sample of 5, 236 adolescent females drawn from Waves I and II, results show that teenage pregnancy is a significant predictor of depression and substance use involvement. Furthermore, a 3-way-interaction effect was observed, specifically teenage pregnancy, association with deviant peers, and depression was a significant predictor of substance use behaviors. Implications for theory, research, and social programs for teen parents are discussed.